Sustainability Analysis of the Creative Economy of Weaved Crafts: A Monte Carlo Model - M. Rudi Irwansyah; Sachiko Ohno; Kadek Rai Suwena; Komang Krisna Heryanda; Diota Prameswari Vijaya (Universitas Negeri Malang, 2024)
The majority of individuals residing in Tigawasa Village, located in the Banjar District of Buleleng Regency in Bali, have been engaging in the traditional craft of bamboo weaving for many generations. This pastime is commonly practiced in nearly all households, engaging the majority of family members. It is crucial to conserve and enhance the village's significant capacity to make high-quality woven goods in order to maximize the community's welfare. This study investigates the assessment of the sustainability of the creative economy of woven bamboo crafts across various dimensions, including economic, social, environmental, institutional, and behavioral aspects. The research used Multi-Dimensional Scaling and Monte Carlo analysis, which are incorporated into the Rapfish software update. The investigation reveals that the sustainability index for the dimensions of economic, social, environmental, and entrepreneurial behavior falls within the moderate group. However, the softness factor is classified as less sustainable. To enhance the sustainability index of the creative economy of bamboo-woven crafts in Tigawasa Village, it is necessary to implement interventions that leverage factors in each dimension. Keywords: Bali crafting, Traditional craft, Creative economy, Sustainability